2013
DOI: 10.1155/2013/102972
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Biogenic Iron Minerals in a Methane Oxidizing Microbial Mat

Abstract: The syntrophic community between anaerobic methanotrophic archaea and sulfate reducing bacteria forms thick, black layers within multi-layered microbial mats in chimney-like carbonate concretions of methane seeps located in the Black Sea Crimean shelf. The microbial consortium conducts anaerobic oxidation of methane, which leads to the formation of mainly two biomineral by-products, calcium carbonates and iron sulfides, building up these chimneys. Iron sulfides are generated by the microbial reduction of oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The formation of iron sulfides at low pH during sulfate reduction with lactate and at high pH during sulfate reduction with formate and hydrogen agrees with other studies (Donald and Southam, 1999). Greigite and elemental sulfur are among the sulfur minerals found at marine cold seeps within or near the SMTZ where their formation is thought to result from the activities of SRB (Lin et al, 2015;Wrede et al, 2013).…”
Section: Mineral Precipitation During Sulfate Reduction 450supporting
confidence: 89%
“…The formation of iron sulfides at low pH during sulfate reduction with lactate and at high pH during sulfate reduction with formate and hydrogen agrees with other studies (Donald and Southam, 1999). Greigite and elemental sulfur are among the sulfur minerals found at marine cold seeps within or near the SMTZ where their formation is thought to result from the activities of SRB (Lin et al, 2015;Wrede et al, 2013).…”
Section: Mineral Precipitation During Sulfate Reduction 450supporting
confidence: 89%
“…On the other hand, members of the phylum Euryarchaeota are directly involved in carbon metabolism, with several classes of methanogens and methane-oxidizing organisms [ 66 68 ]. Navarrete et al [ 48 ] studied the impact of converting Amazon native forest to pasture and reported changes not only to the composition and abundance of soil microbial communities but also to a decrease in the diversity of gene function.…”
Section: Discussionmentioning
confidence: 99%